Following the muon track of hierarchical sectors at LHCb - Xabier Cid Vidal; Titus Mombächer; Ramos, Maria; Emilio Xosé Rodríguez Fernández (arXiv.org, 2022)
This paper reports a study of the experimental signatures of hierarchical sectors beyond the Standard Model characterized by a flavor-violating heavy vector and a set of light pseudo-Goldstone bosons \(a_{1,2}\), spanning a large range of lifetimes. The non-minimal scalar spectrum triggers novel \(B\) decays into multiple leptons that would have escaped the reach of current searches. Novel displaced vertex analyses at LHCb are therefore discussed to probe the hierarchical new physics, extending the scope of the tracking system of the detector. Additionally, the reach of the proposed CODEX-b experiment is studied as well. By exploiting the use of tracks only reconstructed in subsystems of the detector at the high-level LHCb trigger, \({\mathcal{B}(B_s^0→ a_1 a_2) < 10^{-8}}\) and \({\mathcal{B}(B^+→ K^+ a_1 a_2) < 10^{-9}}\) could be reached in the muon channel across seven orders of magnitude in the lifetime of the Goldstone bosons. Correspondingly, heavy-light particle couplings of order \(\lesssim 1\) could be tested, potentially ruling out composite Higgs scenarios where the heavy and light sectors couple strongly.